As concepções de Ciência de licenciandos da UFSCar campus Sorocaba no curso de Química - Oliveira, Nicolas Rosa Gracia (Universidade Federal de São Carlos, 2020)
This work sought to understand what the viewpoints of students enrolled in the Full Degree in Chemistry at UFSCar Campus Sorocaba in the first semester of 2020 about Science and the production of scientific knowledge are. The analysis was made by reviewing specialized literature about the various forms of human knowledge, the main distorted views about science and a questionnaire answered by undergraduate students. The results obtained revealed which is the main distorted view that the group of students has greater affinity, which is the one that points to science as rigid and fragmented. Finally, the paper discusses whether there is a relationship between the visions and the semesters that the students are taking, or even if their participation in events with themes that encompass scientific knowledge impacts students to reduce their distorted visions
The UFSCAR"s studens conceptions in the course of Chemistry
Keywords: Percepção da Ciência. Química. Visões e Distorção; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO